2005
DOI: 10.4310/jsg.2005.v3.n4.a6
|View full text |Cite
|
Sign up to set email alerts
|

Moment maps, symplectomorphism groups and compatible complex structures

Abstract: Abstract. In this paper we apply Donaldson's general moment map framework for the action of a symplectomorphism group on the corresponding space of compatible (almost) complex structures to the case of rational ruled surfaces. This gives a new approach to understanding the topology of their symplectomorphism groups, based on a result of independent interest: the space of compatible integrable complex structures on any symplectic rational ruled surface is (weakly) contractible. We also explain how in general, u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(13 citation statements)
references
References 18 publications
1
12
0
Order By: Relevance
“…One needs to check that standard deformation theory can in fact be used here, in the context of compatible complex structures. This, together with points (vi) and (viii), is proved in [7]. Point (iv) is proved in [12].…”
Section: Symplectomorphism Groups and Compatible Complex Structuressupporting
confidence: 55%
See 2 more Smart Citations
“…One needs to check that standard deformation theory can in fact be used here, in the context of compatible complex structures. This, together with points (vi) and (viii), is proved in [7]. Point (iv) is proved in [12].…”
Section: Symplectomorphism Groups and Compatible Complex Structuressupporting
confidence: 55%
“…It implies, by standard equivariant cohomology theory (see [7]), the following corollary. Contractibility of X λ .…”
Section: Symplectomorphism Groups and Compatible Complex Structuresmentioning
confidence: 78%
See 1 more Smart Citation
“…(This was first proved by Audin [4] and Ahara-Hattori [3]; see also Karshon [19].) Moreover the homotopy type of Ham is understood when M = CP 2 or S 2 × S 2 or a one point blow up of such; see for example Gromov [15], Abreu-McDuff [2], Abreu-GranjaKitchloo [1] and Lalonde-Pinsonnault [28]. For work on nonHamiltonian S 1 actions in dimensions 4 and above see Bouyakoub [6], Duistermaat-Pelayo [7] and Pelayo [50].…”
Section: Introductionmentioning
confidence: 99%
“…He also showed that, restricted to the space I ω of compatible integrable structures, this action fits into the general framework of infinite dimensional geometric invariant theory, going back to Atiyah and Bott [AB1] (see [AK1 ] for more discussion of this point of view). Therefore, in principle, the norm square of the moment map should induce a stratification of I ω with critical points being the extremal Kähler metrics compatible with the symplectic form.…”
Section: Introductionmentioning
confidence: 99%